Mix Freeze group based Cooperative Learning Approach for Improving the Students Reading Comprehension at the first grade students of SMAN 1 Bontomarannu - Sujariati, Sujariati (Universitas Negeri Makassar, 2018)
This research aimed to explain the improvement of the students’ reading comprehension in terms of Literal Reading of the text dealing with main ideas and sequence of details and Creative Reading of the text dealing withcharacterization and conclusion. The researcher used a classroom action research (CAR) which was conducted in two cycles in which every cycle consisted of four meetings. The location of this research was taken at the first grade students of SMAN 1 Bontomarannu with a number of the subject were 35 students. The research findings indicated that the application of SMAN 1 Bontomarannu, This strategy was improving the students’ reading comprehension in terms ofLiteral reading and Creative reading of the text. It was proved by the mean score of cycle I was 60.7. It was classified as fair then improved to be 73.36. It was classified as good in cycle II. They are higher than the mean score of diagnostic test namely 50.7 that classified as poor. Therefore there was the improvement of the students’ reading comprehension in terms of Literal Reading of the text dealing with main ideas and sequence of details and Creative Reading of the text dealing withcharacterization and conclusion.